1967
DOI: 10.2466/pms.1967.25.3.1001
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinations and Disturbances of Affect, Cognition, and Physical State as a Function of Sensory Deprivation

Abstract: A post-isolation interview was administered to 134 Ss confined for up to 72 hr. under three conditions of sensory deprivation: Auditory-Tactual-Visual (Total Deprivation); Auditory-Tactual; and Auditory. Results indicated that Ss were not severely disorganized by the isolation experience. Total deprivation produced greater disturbance of affect and cognition than the two less severely restricted conditions, while complaints of physical discomfort were greater in the latter two groups. Hallucinations were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…First, impaired thalamocortical input to the auditory cortex by itself may have an important role, as AVHs are observed during sensory deprivation 71 . Second, increased synchrony between productive and receptive speech regions, along with reduced suppression of auditory regions during speaking versus listening, may also play a part 72 .…”
Section: Behavioural Consequencesmentioning
confidence: 99%
“…First, impaired thalamocortical input to the auditory cortex by itself may have an important role, as AVHs are observed during sensory deprivation 71 . Second, increased synchrony between productive and receptive speech regions, along with reduced suppression of auditory regions during speaking versus listening, may also play a part 72 .…”
Section: Behavioural Consequencesmentioning
confidence: 99%
“…Both random and systematic biases cannot be excluded at present. Sources: dementia with Lewy bodies (Aarsland et al 2001a;Ballard et al 1995b;, including six reviewed studies; 2001); Parkinson's disease (Aarsland et al 2001a;2001b;Barnes & David 2001;Cummings 1991;Fenelon et al 2000;Goetz 1999;Holroyd et al 2001;Sanchez-Ramos et al 1996); Parkinson's disease plus dementia (Aarsland et al 2001b;Neimark et al 1996); progressive supranuclear palsy (Aarsland et al 2001b); eye disease (Brown & Murphy 1992;Holroyd et al 1992;Kolmel 1993;Lepore 1990;Scott et al 2001;Soros et al 2003); Alzheimer's disease (Ballard et al 1995b;Bathgate et al 2001;Cummings et al 1987;Holroyd & Sheldon-Keller 1995); vascular dementia (Ballard et al 1995b;Bathgate et al 2001;Cummings et al 1987); delirium (Cutting 1997;Webster & Holroyd 2000); sensory deprivation (McKellar 1957;Schulman et al 1967); general population (Lindal et al 1994;Ohayon et al 1996;; occipital stroke (Anderson & Rizzo 1994;Kolmel 1993;Vaphiades et al 1996); people over 85 (Ostling & Skoog 2002); schizophrenia, including paraphrenia (Bracha et al 1989; Cutting 1997;Ndetei & ...…”
Section: Pharmacologically Induced Hallucinationsmentioning
confidence: 99%
“…For example, researchers have identified a correlation between self-awareness and temporal estimates. Individuals who are experimentally deprived of visual, tactile, and/or auditory stimulation and whose primary sensory experiences therefore come from within report that the hours pass more slowly than usual (Schulman et al, 1967). Furthermore, it was demonstrated that both bodily change and awareness of one’s current bodily state positively predict temporal estimates in interval-timing tasks (Meissner and Wittmann, 2011).…”
Section: Sentient Processing Modulates Timementioning
confidence: 99%